Earnings baths by bank CEOs during turnovers - Sven Bornemann; Andreas Pfingsten; Thomas Kick; Andrea Schertler (Deutsche Bundesbank, 2014)
This study investigates the development of income-decreasing discretionary expenses surrounding CEO turnovers at banks. We expect incoming CEOs to take an earnings bath during the initial stage of their tenure. For a sample of German banks over the period 1993-2012, we document that (1) incoming CEOs increase discretionary expenses, i. e. engage in big bath accounting, during their first (partial) year in charge, (2) incoming CEOs from outside the bank take a larger earnings bath than insiders, and (3) incoming CEOs take a smaller earnings bath when the incumbent CEOs retire than when they leave for other reasons. Our findings are robust to several modifications. Most importantly, they also hold true when the incoming CEO's objective of rectifying shortages in the existing stock of risk provisions has been taken into account, which may provide an alternative explanation for observing extraordinary amounts of discretionary expenses in turnover years.
Keywords: C23; G21; M41; 330; CEO turnover; Earnings management; Big bath accounting; Discretionary expenses; Financial institutions